2023
DOI: 10.3390/pharmaceutics15030991
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Anti-Biofilm and Pro-Migratory Effects of Double Layered Hydrogels Packaged with Lactoferrin-DsiRNA-Silver Nanoparticles for Chronic Wound Therapy

Abstract: Antimicrobial resistance and biofilm formation in diabetic foot infections worsened during the COVID-19 pandemic, resulting in more severe infections and increased amputations. Therefore, this study aimed to develop a dressing that could effectively aid in the wound healing process and prevent bacterial infections by exerting both antibacterial and anti-biofilm effects. Silver nanoparticles (AgNPs) and lactoferrin (LTF) have been investigated as alternative antimicrobial and anti-biofilm agents, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…On the other hand, silver-based antimicrobial agents have been prepared with the development of AgNPs and nanocluster preparation techniques. These AgNPs have an ultrasmall hydrodynamic diameter (HD) (smaller than 5.5 nm, the renal filtration threshold) and can be rapidly eliminated through the urine system in a reasonable time, reducing the risk of long-term cytotoxicity. Long-term studies have demonstrated that metallic silver possesses antimicrobial characteristics, and a recent study has shown that low concentrations of silver are not harmful to human cells. , The main cause of AgNP toxicity is their accumulation in cell culture media, cellular uptake, and intracellular localization . According to the results of the current study, numerous variables affect the dangerous limit concentration of AgNPs, including their size, shape, concentration, and surface area.…”
Section: Antimicrobial Applications Of Aunps and Agnpsmentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, silver-based antimicrobial agents have been prepared with the development of AgNPs and nanocluster preparation techniques. These AgNPs have an ultrasmall hydrodynamic diameter (HD) (smaller than 5.5 nm, the renal filtration threshold) and can be rapidly eliminated through the urine system in a reasonable time, reducing the risk of long-term cytotoxicity. Long-term studies have demonstrated that metallic silver possesses antimicrobial characteristics, and a recent study has shown that low concentrations of silver are not harmful to human cells. , The main cause of AgNP toxicity is their accumulation in cell culture media, cellular uptake, and intracellular localization . According to the results of the current study, numerous variables affect the dangerous limit concentration of AgNPs, including their size, shape, concentration, and surface area.…”
Section: Antimicrobial Applications Of Aunps and Agnpsmentioning
confidence: 81%
“…138−142 Long-term studies have demonstrated that metallic silver possesses antimicrobial characteristics, and a recent study has shown that low concentrations of silver are not harmful to human cells. 143,144 The main cause of AgNP toxicity is their accumulation in cell culture media, cellular uptake, and intracellular localization. 145 According to the results of the current study, numerous variables affect the dangerous limit concentration of AgNPs, including their size, shape, concentration, and surface area.…”
Section: Antimicrobial Applications Of Aunps and Agnpsmentioning
confidence: 99%
“…However, Fathil et al successfully formed AgLTF by complexing AgNPs with LTF and utilized this for the targeted therapy of diabetic wounds by loading DsiRNA. 104 The negatively charged DsiRNA was adsorbed onto AgLTF to silence the prostaglandin transporter (PGT) and promote wound healing. Although this study did not employ AgNPs as a drug carrier, the successful adsorption of DsiRNA onto AgLTF demonstrates the potential use of AgNPs as carriers in future applications beyond their antibacterial properties.…”
Section: Research and Application Of Mnps In Wound Healingmentioning
confidence: 99%
“…To address this issue, researchers have successfully developed various novel and effective antimicrobial hydrogels. 281–283 Cai et al developed a eucalyptus essential oil nanoemulsion hydrogel specifically for this purpose. In vitro experiments demonstrated that the hydrogel displayed strong antimicrobial activity and inhibited biofilm formation.…”
Section: Application Of Hydrogel-based Dressings In Different Types O...mentioning
confidence: 99%